Decoding Brand Image, Price, and Location in Determining Noodle Sales in Indonesia (Mengurai Citra Merek, Harga dan Lokasi dalam Menentukan Penjualan Mie di Indonesia) - Hariasih, Misti; Yuniar, Anisya Noorvita (Indonesian Journal Publisher, 2024)
This research was conducted to determine the effect of brand image, price perception, and location on the purchase of Mie Gacoan Sidoarjo. This research is quantitative with the population in this study being consumers of Mie Gacoan Sidoarjo. Random sampling is the method used for sampling, and it means that each population has an equal chance of being included in the sample. Based on the research methodology, the purchasing decision of Mie Sidoarjo is positively and significantly influenced by brand image. Purchase decision is influenced positively and significantly by price. Purchase decisions are positively and significantly influenced by location.